Housing in Portugal (1992-2008) a multidimensional perspective on the behaviour of economic agents - Santos, António Duarte (2022)
Since the nation joined the European Union, the process that regulates housing policy in Portugal has been subject to specificities that are proper of the Portuguese situation. In a State which has a considerable housing deficit, it was the quantifier elements that judged the various governments regarding this matter. Almost all of the housing production depended on mortgage loans in which soft loans played an important part, together with tax benefits. The negative effects produced by lease blocking were increasingly felt throughout the analyzed period of time. The changes in context due to the decrease of tax rates and the legislative alterations on soft loans, conditioned the agents behavior and, necessarily, the rhythm of Portugal’s housing market. Using the STATIS (Structuration of Tableaux A Trois Indices de la Statistique) methodology and through the analysis of the housing policy instruments, it was possible to identify the trajectories and changes in performance of the State, Owners and Families during the period between 1992 and 2008, as well as the most significant variables for understanding the problematic of housing in Portugal.